Management Practices Is Not Important For Women Entrepreneurs In Family Business While Enhance Their Business Performance: Evidence From Melaka, Malaysia. - Wahjono, Sentot Imam; Abdul Hamid, Harnida Hanim; Adilah , Mohd Din; Saleh, Hasan (2014)
The aim of this paper is to investigate what is the factor of women entrepreneur in family business that can gain the business performance. This research is to focus the how the business performance will give changes in overall business management that increase their business performance. This research use quantitative analysis, involves 150 respondent that have own business in Melaka. The findings, it stated of all factor of women entrepreneur in family business to enhance business performance. The important factors of women entrepreneur to enhance business performance are goals and motivation, individual factor, and networking. While management practices is not important. The Implication of this research is, need to focus on strengthening the motivation and networking in particular to increase sales and profits rather than to counseling, and educational courses to improve management practices.